Dysregulation of Transcription Factor Networks Unveils Different Pathways in Human Papillomavirus 16-Positive Squamous Cell Carcinoma and Adenocarcinoma of the Uterine Cervix - Bispo, Saloe; Farias, Ticiana D. J.; de Araujo-Souza, Patricia Savio; Cintra, Ricardo; Santos, Hellen Geremias dos; Jorge, Natasha Andressa Nogueira; Castro, Mauro Antônio Alves; Wajnberg, Gabriel; Scherer, Nicole de Miranda; Genta, Maria Luiza Nogueira Dias; Carvalho, Jesus Paula; Villa, Luisa Lina; et al. (Frontiers in Oncology, 2021)
Squamous cell carcinoma (SCC) and adenocarcinoma (ADC) are the most common histological types of cervical cancer (CC). The worse prognosis of ADC cases highlights the need of better molecular characterization regarding differences between these CC types. RNA-Seq analysis of 7 SCC and 3 ADC human papillomavirus (HPV)-16 positive samples, and the comparison with public data from non-tumoral HPV negative cervical tissue samples revealed pathways exclusive to each histological type, such as the epithelial maintenance in SCC and the maturity-onset diabetes of the young pathway (MODY) in ADC. The transcriptional regulatory network (TRN) analysis of cervical SCC samples unveiled a set of six transcription factor (TF) genes with potential to positively regulate long non-coding RNA genes DSG1-AS1, CALML3-AS1, IGFL2-AS1 and TINCR. Additional analysis revealed a set of MODY TFs regulated in sequence predicted to be repressed by miR-96-5p or miR-28-3p in ADC. These miRNAs were previously described to target LINC02381, that was predicted to be positively regulated by two MODY TFs upregulated in cervical ADC. Therefore, we hypothesize LINC02381 might act decreasing the levels of miR-96-5p and miR-28-3p, promoting the MODY activation in cervical ADC. The novel TF networks here described should be explored for the development of more efficient diagnostic tools.